A new hydrogen world: Geotechnological, economic, and political implications for Europe - Julian Grinschgl; Jacopo Maria Pepe; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2021)
The global implications of a switch to hydrogen (H2) are far-reaching, as hydrogen will, at least in part, gradually replace the oil and gas trade, and new international trade flows will emerge. In addition, hydrogen will transform the industry, and its use will have disruptive effects that reshape the economic geography. Policymakers are being called upon to make far-reaching, fundamental decisions that will decisively shape the contours of the hydrogen world. Germany and the European Union (EU) should consider the geo-economic and political consequences when setting the course.
Keywords: 330